Ramie (Boehmeria nivea) Plant Nutrient Quality as Feed Forage at Various Cut Ages - Suryanah, Sari; Rochana, Ana; Susilawati, Iin; Indiriani, Nyimas Popi (ANIMAL PRODUCTION, 2017)
This study was aimed to determine the nutrient quality of the ramie plant (Boehmeria nivea) at various cut ages. The research was conducted in the village of Kampung Marga Marga Mulya Bakti RT. 01 RW. 13 Cikandang districts, Garut. The design used was completely randomized design with four (4) treatments and five (5) replications, namely; the treatment of 15-days cutting-age, 30-days cutting-age, 45-days cutting-age, and 60-days cutting-age. The results showed that the cutting age had significant effect (p <0.05) on crude protein, crude fiber content, and the lignin content of ramie forage. The older cutting age had the decreased crude protein content, while increased the crude fiber and lignin content. The best cutting age of ramie plant as forage for optimal nutrients quality was 30 days.